William Shakespeare's the clone army attacketh : Star Wars part the second - Doescher, Ian; Lucas, George, 1944- (Quirk Books, 2015)
A retelling of The attack of the clones in iambic pentameter, the style of Shakespeare. Between duty to the Jedi, attraction to Padmé, and concern for his beloved mother, yeoman Jedi Anakin Skywalker struggles to be master of his fate. The path he chooses will determine not just his own destiny, but that of the entire Republic. Alack the day!